Perbandingan Proporsi Antibodi Ireguler pada Pasien Multitransfusi dan Pasien Non Multitransfusi di UTD RSUP Dr. Mohammad Hoesin Palembang - Amalia Amalia; Zen Hafy; Phey Liana (Jurnal Surya Medika (JSM), 2021)
Irregular antibodies or "unexpected antibodies" are antibodies other than antibody A and antibody B that can occur due to pregnancy and blood transfusions. Patients who frequently perform transfusions (multitransfusions) are more at risk of forming irregular antibodies because the frequency of exposure to donor red blood cell antigens is more frequent. Irregular antibodies are clinically significant because they can cause hemolysis (erythrocyte alloantibodies), febrile non-hemolytic transfusion reactions (leukocyte alloantibodies), or refractory platelet transfusions (platelet alloantibodies). This research aims to compare the proportion of irregular antibodies in multitransfusion patients and non-multi transfused patients at UTD Dr. Mohammad Hoesin Palembang. This research is an analytic observational study with a cross-sectional design conducted on 2 groups of subjects, 45 each sample. Antibody identification in each group was carried out. Chi-Square analyzed the proportion of irregular antibodies. An analysis of the types of antibodies found and the accompanying clinical diagnoses were carried out. This study showed a significant difference in the proportion of irregular antibodies between the multitransfusion and non-multitransfusion groups with a p-value of 0.001. The types of irregular antibodies found anti-c, Fya, Lea, M, Kpa, LubkKpb, and the clinical diagnoses that found irregular antibodies were anemia, thalassemia, and AIHA.